Robust efficient cruise control for heavy haul train via the state-dependent intermittent control. (November 2020) - Wang, Xi; Li, Shukai; Tang, Tao
Abstract: Heavy haul railway plays an important role in providing the convenient and economical services for mass goods transportation. In order to improve the efficiency of heavy haul train transportation, the driving strategy should be developed for the heavier and longer trains correspondingly. This paper addresses the robust efficient intermittent cruise control problem for heavy haul train with uncertain parameters and external disturbances. Inspired by the experience of expert drivers, we design the activated mechanism for the control input under the framework of state-dependent intermittent control, which is distinguished from the traditional continuous train control methods in that the control command is only exerted when the train states satisfy certain conditions. Considering the characteristics of heavy haul train movement, parameters uncertainty and external disturbances are both taken into account in the train state-space dynamic model. On the basis of Lyapunov stability approach and H ∞ theory, a series of linear matrix inequalities (LMIs) are introduced as the sufficient conditions for the existence of the robust efficient state-dependent intermittent cruise controller, which can guarantee both the velocity tracking error and the relative coupler displacement between the two connected cars are stable at the equilibrium state with a prescribed H ∞ disturbance attenuation level. Numerical examples are presented to illustrate the effectiveness of the proposed controller.